Student Difficulties and Teacher Strategies in Learning Accounting Spreadsheets: Kesulitan Siswa dan Strategi Guru dalam Mempelajari Spreadsheet Akuntansi - Pangestuti, Diyana; Asmawan, Moh. Chairil (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to find out: 1) types of student learning difficulties in learning Accounting Spreadsheet at SMK Negeri 1 Salatiga, 2) factors causing learning difficulties, and 3) teacher strategies in overcoming these difficulties. This research uses a qualitative method with a case study approach. Data collection techniques include interviews, observation, and documentation, with triangulation techniques for data validity. The stages of data analysis include data reduction, data presentation, and conclusion drawing. The results showed that: (1) the types of student difficulties are classified as moderate, namely lack of understanding in operating computers and difficulty memorising spreadsheet formulas. (2) Factors causing learning difficulties consist of internal factors such as limited understanding in using computers and memorising formulas, and external factors such as not having a personal laptop and unsupportive devices. (3) Teachers‘ strategies to overcome students’ difficulties include applying learning methods using room passwords and providing routine practice questions. Highlights: Moderate Student Challenges – Students struggle with using computers and memorizing spreadsheet formulas. Internal & External Factors – Issues stem from limited skills and lack of personal tech devices. Teacher Solutions – Applied room password methods and frequent practice to aid learning. Keywords: Learning Difficulties, Teaching Strategies, Spreadsheet